2016
DOI: 10.18632/oncotarget.6830
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced lncRNA-NUTF2P3-001 contributes to tumorigenesis of pancreatic cancer by derepressing the miR-3923/KRAS pathway

Abstract: Recent studies indicate that long non-coding RNAs (lncRNAs) play crucial roles in numerous cancers, while their function in pancreatic cancer is rarely elucidated. The present study identifies a functional lncRNA and its potential role in tumorigenesis of pancreatic cancer. Microarray co-assay for lncRNAs and mRNAs demonstrates that lncRNA-NUTF2P3-001 is remarkably overexpressed in pancreatic cancer and chronic pancreatitis tissues, which positively correlates with KRAS mRNA expression. After downregulating ln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 43 publications
0
70
0
2
Order By: Relevance
“…Multivariate analysis showed that a high MTA2 protein level was an independent prognostic factor for lower overall survival of pancreatic carcinoma patients [18]. MTA2 was correlated with tumour invasion and tumour embolus formation in gastric carcinoma, and trapping MTA2 in the cytosol or knockdown of MTA2 inhibited growth and metastasis [28]. MTA2 is an independent prognostic factor for the survival of colorectal carcinoma patients, and high MTA2 expression correlated with poor overall survival [29].…”
Section: Mta2 and Hdac1 Are Critical For Hypoxia-induced Reduction Ofmentioning
confidence: 99%
“…Multivariate analysis showed that a high MTA2 protein level was an independent prognostic factor for lower overall survival of pancreatic carcinoma patients [18]. MTA2 was correlated with tumour invasion and tumour embolus formation in gastric carcinoma, and trapping MTA2 in the cytosol or knockdown of MTA2 inhibited growth and metastasis [28]. MTA2 is an independent prognostic factor for the survival of colorectal carcinoma patients, and high MTA2 expression correlated with poor overall survival [29].…”
Section: Mta2 and Hdac1 Are Critical For Hypoxia-induced Reduction Ofmentioning
confidence: 99%
“…Dysregulated lncRNAs expression in cancer tissues correlates with the spectrum of disease progression and may be regarded as a predictor of patient outcomes . Recently, several lncRNAs have been reported to participate in hypoxia‐associated cancer biology, implying a potential role of lncRNA in maintaining cellular homeostasis and enabling adaptive survival under hypoxia . Mineo et al identified hypoxia‐inducible factor 1 alpha‐antisense RNA 2 (HIF1A‐AS2) as a subtype specific hypoxia‐inducible lncRNA, up‐regulated in mesenchymal glioblastoma multiforme stem‐like cells.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Recently, several lncRNAs have been reported to participate in hypoxiaassociated cancer biology, implying a potential role of lncRNA in maintaining cellular homeostasis and enabling adaptive survival under hypoxia. [19][20][21][22] Mineo et al 23 identified hypoxia-inducible factor 1 alphaantisense RNA 2 (HIF1A-AS2) as a subtype specific hypoxia-inducible lncRNA, up-regulated in mesenchymal glioblastoma multiforme stemlike cells. Deregulation of HIF1A-AS2 interferes with cell growth, self-renewal, and hypoxia-dependent molecular reprogramming.…”
mentioning
confidence: 99%
“…Increasing evidence has suggested that long non-coding RNAs (lncRNAs) serve multiple functions in tumor initiation and development, and represent novel targets for cancer diagnosis and therapies (5,6). Several lncRNAs have been associated with pancreatic cancer and may be used as biomarkers of PDAC (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%